Role of burn severity and posttraumatic stress symptoms in the co-occurrence of itch and neuropathic pain after burns: A longitudinal study - Van Loey, N. E. E.; de Jong, A. E. E.; Hofland, H. W. C.; van Laarhoven, A. I. M. (Frontiers in Medicine, 2022)
Itch and pain are common after burns. Neuropathic mechanisms may underlie both modalities but remain not well-understood. This study aims to prospectively document neuropathic pain symptoms and to identify potential itch symptom profiles that differ regarding duration and co-occurrence with neuropathic pain which may inform underlying pathophysiological mechanisms and respond to different treatments. Adult burn survivors (n = 192) self-reported itch and neuropathic pain at 2 weeks post-discharge, 3, 6, 12, and 18 months post-burn. Based on their itch symptom reports, participants were allocated to one itch profile: transient itch/pain, chronic itch, or chronic itch & pain. Profiles were compared on itch intensity over time using General Linear Modeling. Age, gender, burn severity, posttraumatic stress (PTS) symptoms and baseline itch intensity were examined as potential predictors of the profiles in a Multi-nominal regression analysis. Neuropathic pain occurred in 54% after discharge which decreased to 24% 18 months later. One hundred twenty-five participants could be allocated to an itch profile. Itch intensity was highest in the chronic itch & pain profile. Compared to the transient profile, the chronic itch & pain profile was associated with higher burn severity and more PTS symptoms. Compared to the chronic itch profile, the chronic itch & pain profile was associated with more PTS symptoms. This suggests that biological and psycho-dermatological processes underlie both neuropathic pain and itch processes in burn scars. Further research should elucidate the mechanisms underlying the different itch profiles, with specific focus on skin innervation and psychological factors.